Actualization of Sample Education Language in Character Education Towards Era Millennial MIN Sambas District - Purniadi Putra; Hadisa Putri (The Pontianak State Institute of Islamic Studies, 2021)
The purpose of this study was to describe the meaning of Sambas Malay language in effectively instilling character education in the millennial era at Sambas Regency State Islamic School. This research is important because today there are many phenomena that occur attitudes and behaviors and language that are less polite among students and the younger generation today. This research method uses qualitative phenomologic. The research focus of the madrasa principals, teachers and students. Data analysis techniques use multi-site studies that are used to develop a theory of broader situations. The results of this study indicate that MIN applies Sambas Malay language by familiarizing students in speaking. The meaning of Usah Nak Nyuppane's expression in Character Education means not to embarrass friends with the value of friendly character. The expression of the kacik of the palm of the hand, we imply (the small palm of the hand, the greeting we present) means to show a great attitude of sincerity with the value of character tolerance. The attitude and manners shown in the madrasa in accordance with the process of inheritance of the value of education instilled through the tradition of the word